Immunomodulatory properties of dental tissue‐derived mesenchymal stem cells. (6th March 2013) - Li, Z; Jiang, C‐M; An, S; Cheng, Q; Huang, Y‐F; Wang, Y‐T; Gou, Y‐C; Xiao, L; Yu, W‐J; Wang, J
<x xml:space="preserve">Abstract</x> In addition to their well‐established self‐renewal and multipotent differentiation properties, mesenchymal stem cells (MSCs) also possess potent immunomodulatory functions both in vitro and in vivo, which render them a potential novel immunotherapeutic tool for a variety of autoimmune and inflammation‐related diseases. The major mechanisms may involve (1) the secretion of an array of soluble factors such as prostaglandin E2 (PGE2), indoleamine 2, 3‐dioxygenase (IDO), transforming growth factor‐β (TGF‐β), and human leukocyte antigen G5 (HLA‐G5); (2) interactions between MSCs and immune cells such as T cells, B cells, macrophages, and dendritic cells. Recently, increasing evidence has supported that MSCs derived from dental tissues are promising alternative sources of multipotent MSCs. We here provide a thorough and extensive review about new findings in the immunomodulatory functions of MSCs derived from several dental tissues, including dental pulp, periodontal ligament, gingiva, exfoliated deciduous teeth, apical papilla, and dental follicle, respectively. The immunomodulatory properties of dental MSCs place them as a more accessible cell source than bone marrow‐derived MSCs for cell‐based therapy of immune and inflammation‐related diseases.